ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2022
DOI: 10.1109/icassp43922.2022.9747498
|View full text |Cite
|
Sign up to set email alerts
|

Superresolution and Segmentation of OCT Scans Using Multi-Stage Adversarial Guided Attention Training

Abstract: Optical coherence tomography (OCT) is one of the noninvasive and easy-to-acquire biomarkers (the thickness of the retinal layers, which is detectable within OCT scans) being investigated to diagnose Alzheimer's disease (AD). This work aims to segment the OCT images automatically; however, it is a challenging task due to various issues such as the speckle noise, small target region, and unfavorable imaging conditions. In our previous work, we have proposed the multi-stage & multi-discriminatory generative adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…By using different perspectives to discriminate the importance of different contextual spectral information, each way has its unique advantage in boosting network performance. For instance, previous studies [27,28] have found that channel attention can find out which channel feature information is crucial for training and thus reassign weights to feature vectors of different channels. Spatial attention usually flexibly weights feature information according to the importance of its spatial location.…”
Section: Triple-attention-based Tcnn (Ta-tcnn)mentioning
confidence: 99%
“…By using different perspectives to discriminate the importance of different contextual spectral information, each way has its unique advantage in boosting network performance. For instance, previous studies [27,28] have found that channel attention can find out which channel feature information is crucial for training and thus reassign weights to feature vectors of different channels. Spatial attention usually flexibly weights feature information according to the importance of its spatial location.…”
Section: Triple-attention-based Tcnn (Ta-tcnn)mentioning
confidence: 99%